Investigating the Role of Having an Avatar in Virtual Reality on Pain Alleviation and Embodiment in Patients With Pain Using Electroencephalogram: A Neuroimaging Protocol - Kiaei Ziabari, Seyedeh Pegah; Ofoghi, Zahra; Rodrigues, Emma A.; Gromala, Diane; Moreno, Sylvain (Frontiers in Virtual Reality, 2022)
Chronic Pain (CP) is prevalent in industrialized countries and stands among the top 10 causes of disability. Given the widespread problems of pharmacological treatments such as opioids, a need to find alternative therapeutic approaches has emerged. Virtual Reality (VR) has shown potential as a non-pharmacological alternative for controlling pain over the past 20 years. The effectiveness of VR has been demonstrated in treating CP, and it has been suggested that VR’s analgesic effects may be associated with a Sense of Embodiment (SoE): the sensation of being inside, having and controlling a virtual body in VR. Studies have shown correlations among brain signals, reported pain and a SoE, and correlations have been observed between using an avatar in VR and pain alleviation among CP patients. However, little has been published about the changes in brain physiology associated with having an avatar in VR, and current published studies present methodological issues. Defining a proper methodology to investigate the underlying brain mechanisms of pain, a SoE associated with having an avatar in VR, and its effect on reducing pain in CP patients is key to the emerging field of VR-analgesia. Here, we propose an intervention trial design (test/intervention/test) to evaluate the effects of having a virtual avatar in VR on pain levels and SoE in CP patients using Electroencephalogram (EEG) recordings. Resting-state EEG recordings, perceived pain levels, and SoE scores will be collected before and after the VR intervention. Patients diagnosed with CP will be recruited from local pain clinics and pseudo-randomly assigned to one of two groups – with or without an avatar. Patients will experience a 10-minute VR intervention built to treat CP while their EEG signals are recorded. In articulating the study procedure, we propose a framework for future studies that explores the mechanisms of VR-analgesia in patients with chronic pain